Histology a text and atlas : with correlated cell and molecular biology - Ross, Michael H.; Pawlina, Wojciech (Wolters Kluwer Health, 2016)
Now in its seventh edition, Histology: A Text and Atlas is ideal for medical, dental, health professions, and undergraduate biology and cell biology students. This best-selling combination text and atlas includes a detailed textbook, which emphasizes clinical and functional correlates of histology fully supplemented by vividly informative illustrations.